A high-toughness silicon carbide ceramic composite material and a method for preparing the same

CN121974700BActive Publication Date: 2026-10-09兰溪泛翌精细陶瓷有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610272881.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-06
Publication Date
2026-10-09
Estimated Expiration
2046-03-06

AI Technical Summary

Technical Problem

然而,此类传统技术普遍面临三大瓶颈:其一,增强相分散性差:纳米或微米级的增强体在粉末混合过程中极易发生团聚,这些团聚体在烧结后会成为材料内部的原始缺陷,非但难以实现预期的增韧效果,反而会恶化材料的力学性能;其二,增韧作用单一且效率有限:传统复合材料往往只依赖于裂纹偏转或桥联等一两种有限的增韧作用,其协同效应不足,导致韧性提升效果难以突破瓶颈;其三,界面调控困难:增强相与基体间的界面结合状态对增韧效果至关重要,但传统方法难以对界面进行主动设计和精确调控,导致晶须拔出等高效增韧作用难以充分发挥

Benefits of technology

[0053] In the early stages of sintering, the self-made yttrium-lanthanum dual rare earth boride additive reacts with the silica on the surface of silicon carbide to form a low-melting-point Y-La-Si-OB liquid phase. This liquid phase encapsulates the particles and promotes mass transfer, which not only helps the material to densify at relatively low temperatures, but also creates the necessary conditions for the in-situ generation of various reinforcing phases.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a high-toughness silicon carbide ceramic composite material and a preparation method thereof, and belongs to the technical field of ceramic composite materials; necessary conditions are created for subsequent reactions by in-situ formation of a low-eutectic liquid phase of yttrium-lanthanum double rare earth borides; in this environment, TiB X The synergistic reaction of the Ti-C precursor and the graphene quantum dot@silicon nitride composite powder can form a multi-scale reinforcing structure in the material, which is formed by titanium carbide / β-silicon nitride whiskers as a skeleton and boron carbide particles dispersed therein; in the aspect of interface regulation, the carbon layer converted from the graphene quantum dots forms a relatively weak interface around the whiskers, thereby being beneficial to the play of the whisker pull-out effect, and promoting the formation of two-dimensional boron nitride layers to introduce a crack deflection effect; when the crack expands, its energy can be cooperatively dissipated by the processes of particle pinning, crack deflection, whisker bridging and pull-out, thereby realizing the high toughness of the material, and thus the application is suitable for the field of green special refractory ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic composite materials technology, and relates to a high-toughness silicon carbide ceramic composite material and its preparation method, which is applicable to the field of green special refractory ceramics. Background Technology

[0002] Silicon carbide ceramics, as a type of special refractory ceramic material, have broad application prospects in cutting-edge fields such as aerospace, high-end equipment manufacturing, and nuclear industry due to their high hardness, excellent high-temperature strength, corrosion resistance, and oxidation resistance. However, their inherent covalent bond structure leads to high intrinsic brittleness and low fracture toughness, a weakness that limits their reliability and application range as structural components. Therefore, developing silicon carbide ceramic composite materials with high toughness is key to expanding their engineering applications.

[0003] Currently, the mainstream technical approach to improving the toughness of silicon carbide ceramics mainly relies on the direct composite of external reinforcing phases, such as adding silicon carbide whiskers / fibers, carbon fibers, or hard particles. However, such traditional technologies generally face three major bottlenecks: First, poor dispersion of the reinforcing phase: nano- or micro-sized reinforcing materials are prone to agglomeration during powder mixing. These agglomerates become original defects inside the material after sintering, which not only fails to achieve the expected toughening effect but also deteriorates the mechanical properties of the material. Second, single and limited toughening effect: traditional composite materials often rely on only one or two limited toughening effects, such as crack deflection or bridging, which are insufficient in their synergistic effect, making it difficult to break through the bottleneck in toughness improvement. Third, difficulty in interface control: the interfacial bonding state between the reinforcing phase and the matrix is ​​crucial to the toughening effect, but traditional methods make it difficult to actively design and precisely control the interface, resulting in the inability to fully exert efficient toughening effects such as whisker pull-out. Summary of the Invention

[0004] To address the aforementioned problems, the present invention aims to provide a high-toughness silicon carbide ceramic composite material and its preparation method. In this application, the yttrium-lanthanum dual rare-earth boride additive can form a low-melting-point liquid phase in situ during sintering. This liquid phase not only helps promote rapid densification of the matrix but also serves as a mass transport medium, creating the necessary conditions for subsequent reactions. In this liquid phase environment, TiB... X-C precursors and graphene quantum dots@silicon nitride composite powders can undergo a synergistic reaction, thereby forming a multi-scale reinforcing structure within the material. In terms of fine-tuning the interface, the nano-carbon layers transformed from graphene quantum dots form a relatively weak bonding interface around titanium carbide whiskers, which is conducive to the toughening effect such as whisker pull-out. On the other hand, it promotes the formation of layered phases such as two-dimensional boron nitride to introduce crack deflection. Finally, when cracks propagate, their energy can be further dissipated through processes such as pinning of nanoparticles, passivation of amorphous phases, deflection of boron nitride sheets, and whisker bridging / pull-out, thereby achieving high toughness.

[0005] To achieve this objective, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a method for preparing a high-toughness silicon carbide ceramic composite material, the method comprising:

[0007] S1: Titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder were ball-milled with anhydrous ethanol at high energy to obtain a precursor mixture slurry; the precursor mixture slurry was vacuum dried to obtain a pre-prepared precursor, which was then heat-treated under an inert atmosphere, naturally cooled, ground, and sieved to obtain TiB. X -C nanocomposite precursor;

[0008] S2: Citric acid and urea were dispersed in deionized water to obtain reaction solution A. After hydrothermal reaction, graphene quantum dot dispersion was obtained after centrifugation and purification. α-Silicon nitride was added to deionized water to prepare α-silicon nitride suspension. The graphene quantum dot dispersion was added dropwise to the α-silicon nitride suspension to obtain reaction solution B. After adjusting the pH value, the mixture was magnetically stirred and vacuum dried to obtain graphene quantum dot@silicon nitride composite powder.

[0009] S3: Yttrium nitrate, lanthanum nitrate, boric acid and citric acid were dispersed in deionized water to obtain a sol; the sol was heated in a water bath and the pH value was adjusted with ammonia to obtain a gel; after drying the gel, it was pre-carbonized under nitrogen protection to obtain a crude product, and the temperature was further increased and held, and after cooling, it was purified to obtain yttrium-lanthanum double rare earth boride solid solution nanoparticles.

[0010] S4: Silicon carbide, TiB X -C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol were wet-mixed with anhydrous ethanol to obtain a composite slurry; the composite slurry was vacuum-dried and sieved to obtain composite granulated powder; the composite granulated powder was loaded into a graphite mold, placed in a spark plasma sintering furnace, and vacuumed; the temperature was raised to the sintering temperature and held, and uniaxial pressure was applied during the heating process; the high-toughness silicon carbide ceramic composite material was obtained by continuing to cool with the furnace under pressure.

[0011] As a preferred technical solution of the present invention, in step S1, the molar ratio of titanium dioxide nanopowder, amorphous boron powder and carbon black powder is 1:(2.1-2.4):(4.5-5.5), for example, it can be 1:(2.1, 2.13, 2.16, 2.19, 2.22, 2.25, 2.28, 2.31, 2.34, 2.37 or 2.4):(4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4 or 5.5), but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0012] In some optional embodiments, the ball milling speed of the titanium dioxide nanopowder, amorphous boron powder, and carbon black powder is 300-400 rpm, for example, 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm, 350 rpm, 360 rpm, 370 rpm, 380 rpm, 390 rpm, or 400 rpm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0013] In some optional embodiments, the ball milling time for the titanium dioxide nanopowder, amorphous boron powder, and carbon black powder is 20-28 hours, for example, 20.0 hours, 20.8 hours, 21.6 hours, 22.4 hours, 23.2 hours, 24.0 hours, 24.8 hours, 25.6 hours, 26.4 hours, 27.2 hours, or 28.0 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0014] In some optional embodiments, the vacuum drying temperature of the precursor mixture slurry is 70-90°C, for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0015] In some optional embodiments, the heating rate of the pre-prepared precursor heat treatment is 4-6℃ / min, for example, it can be 4.0℃ / min, 4.2℃ / min, 4.4℃ / min, 4.6℃ / min, 4.8℃ / min, 5.0℃ / min, 5.2℃ / min, 5.4℃ / min, 5.6℃ / min, 5.8℃ / min or 6.0℃ / min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0016] In some optional embodiments, the temperature of the preformed precursor heat treatment is 900-1000°C, for example, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0017] In some optional embodiments, the heat treatment time of the preform precursor is 1.5-2.5h, for example, it can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h or 2.5h, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0018] As a preferred technical solution of the present invention, in step S2, the mass ratio of citric acid to urea is 1:(1.8-2.2), for example, it can be 1:1.80, 1:1.84, 1:1.88, 1:1.92, 1:1.96, 1:2.00, 1:2.04, 1:2.08, 1:2.12, 1:2.16 or 1:2.20, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0019] In some optional embodiments, the temperature of the hydrothermal reaction of the reaction solution A is 170-190°C, for example, it can be 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 182°C, 184°C, 186°C, 188°C or 190°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0020] In some optional embodiments, the hydrothermal reaction time of the reaction solution A is 6-10 h, for example, it can be 6.0 h, 6.4 h, 6.8 h, 7.2 h, 7.6 h, 8.0 h, 8.4 h, 8.8 h, 9.2 h, 9.6 h or 10.0 h, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0021] In some optional embodiments, the amount of citric acid fed is 5-15% of the mass of α-silicon nitride, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0022] In some alternative embodiments, the pH of the reaction solution B is adjusted to 4-5, for example, to 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0023] In some optional embodiments, the reaction solution B is magnetically stirred for 3-5 hours after pH adjustment, for example, 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h or 5.0h, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0024] In some optional embodiments, the vacuum drying temperature is 70-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0025] As a preferred technical solution of the present invention, in step S3, the molar ratio of yttrium nitrate to lanthanum nitrate is (0.9-1.1):1, for example, it can be 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1, 1:1, 1.02:1, 1.04:1, 1.06:1, 1.08:1 or 1.1:1, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0026] In some alternative embodiments, the total molar amount of yttrium nitrate and lanthanum nitrate is in a molar ratio of 1:(5.8-6.2) to boric acid, for example, 1:5.8, 1:5.84, 1:5.88, 1:5.92, 1:5.96, 1:6, 1:6.04, 1:6.08, 1:6.12, 1:6.16 or 1:6.2, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0027] In some alternative embodiments, the total molar amount of yttrium nitrate and lanthanum nitrate is in a molar ratio of citric acid to 1:(1.4-1.6), for example, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48, 1:1.5, 1:1.52, 1:1.54, 1:1.56, 1:1.58 or 1:1.6, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0028] In some alternative embodiments, the sol is heated in a water bath at 75-85°C, for example, in a water bath at 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0029] In some optional embodiments, the concentration of the ammonia water is 5-15 wt.%, for example, it can be 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, 12 wt.%, 13 wt.%, 14 wt.% or 15 wt.%, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0030] In some alternative embodiments, the sol is heated in a water bath and the pH is adjusted to 7-8, for example, to 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9 or 8.0, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0031] In some optional embodiments, the heating rate for pre-carbonization after gel drying is 2-4 °C / min, for example, it can be 2.0 °C / min, 2.2 °C / min, 2.4 °C / min, 2.6 °C / min, 2.8 °C / min, 3.0 °C / min, 3.2 °C / min, 3.4 °C / min, 3.6 °C / min, 3.8 °C / min or 4.0 °C / min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0032] In some optional embodiments, the temperature for pre-carbonization of the gel after drying is 550-650°C, for example, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0033] In some optional embodiments, the pre-carbonization time after drying of the gel is 1.5-2.5 h, for example, it can be 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h or 2.5 h, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0034] In some alternative embodiments, the rate of heating during further processing of the crude product is 4-6 °C / min, for example, 4.0 °C / min, 4.2 °C / min, 4.4 °C / min, 4.6 °C / min, 4.8 °C / min, 5.0 °C / min, 5.2 °C / min, 5.4 °C / min, 5.6 °C / min, 5.8 °C / min or 6.0 °C / min, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0035] In some optional embodiments, the temperature at which the crude product is further heated is 1400-1500°C, for example, 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, or 1500°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0036] In some optional embodiments, the crude product is kept at a constant temperature for 2.5-3.5 hours after further heating, for example, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours, 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, or 3.5 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0037] As a preferred embodiment of the present invention, in step S4, the mass ratio of silicon carbide, TiBX-C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanopowder, and polyvinyl alcohol is (85-90):(4-6):(2-4):(1.5-2.5):(0.8-1.2), for example, it can be (85, 85.5, 86, 86.5, 87, 87.5, 88, 88.5, 89, 89.5 or 90):(4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4). 5.6, 5.8 or 6.0: (2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8 or 4.0): (1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40 or 2.50): (0.80, 0.84, 0.88, 0.92, 0.96, 1.00, 1.04, 1.08, 1.12, 1.16 or 1.20), but not limited to the listed values; other unlisted values ​​within this range also apply.

[0038] In some optional embodiments, the wet mixing speed is 250-350 rpm, for example, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm or 350 rpm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0039] In some optional embodiments, the wet mixing time is 10-14 hours, for example, 10.0 hours, 10.4 hours, 10.8 hours, 11.2 hours, 11.6 hours, 12.0 hours, 12.4 hours, 12.8 hours, 13.2 hours, 13.6 hours, or 14.0 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0040] In some optional embodiments, the temperature for vacuum drying of the composite slurry is 70-90°C, for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0041] In some optional embodiments, the vacuum degree during sintering of the composite granulated powder is 10. -1 -10 -3 Pa, for example, could be 1.0 × 10 -3 Pa, 1.09×10 -2 Pa, 2.08 × 10 -2 Pa, 3.07×10 -2 Pa, 4.06×10 -2 Pa, 5.05 × 10 -2 Pa, 6.04 × 10 -2 Pa, 7.03×10 -2 Pa, 8.02×10 -2 Pa, 9.01×10 -2 Pa or 1.0 × 10 -1 Pa, but not limited to the listed values, applies to other unlisted values ​​within the same range.

[0042] In some optional embodiments, the heating rate is 80-120°C / min, for example, it can be 80°C / min, 84°C / min, 88°C / min, 92°C / min, 96°C / min, 100°C / min, 104°C / min, 108°C / min, 112°C / min, 116°C / min or 120°C / min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0043] In some optional embodiments, the sintering temperature of the composite granulated powder is 1750-1900℃, for example, it can be 1750℃, 1765℃, 1780℃, 1795℃, 1810℃, 1825℃, 1840℃, 1855℃, 1870℃, 1885℃ or 1900℃, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0044] In some optional embodiments, the time for granulating the composite powder is 6-10 min, for example, it can be 6.0 min, 6.4 min, 6.8 min, 7.2 min, 7.6 min, 8.0 min, 8.4 min, 8.8 min, 9.2 min, 9.6 min or 10.0 min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0045] In some optional embodiments, the uniaxial pressure applied during the composite granulation process is 40-60 MPa, for example, it can be 40 MPa, 42 MPa, 44 MPa, 46 MPa, 48 MPa, 50 MPa, 52 MPa, 54 MPa, 56 MPa, 58 MPa or 60 MPa, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0046] Secondly, the present invention provides a high-toughness silicon carbide ceramic composite material.

[0047] This application utilizes the synergistic effect of multi-component in-situ reactions to construct a multi-scale, multi-mechanism composite toughening structure in a silicon carbide ceramic matrix, thereby improving the toughness of the material.

[0048] First, the construction of a low-temperature liquid phase environment provides the foundation for efficient in-situ reactions and offers the necessary reaction medium and mass transfer conditions for catalysis. The prepared yttrium-lanthanum dual rare-earth boride solid solution nanoparticles react with the native silica layer on the surface of silicon carbide particles during the initial sintering stage, forming a eutectic liquid phase based on the Y-La-Si-OB system. This liquid phase exhibits good wettability, encapsulating the silicon carbide particles and providing a rapid mass transport channel for subsequent solid-phase reactions. This not only effectively reduces the temperature and pressure required for sintering and promotes rapid densification of the matrix, but also provides favorable conditions for the dissolution, migration, and re-precipitation of elements such as titanium, boron, carbon, and nitrogen.

[0049] Secondly, multi-dimensional, multi-scale reinforcing networks can be formed in situ in this liquid environment. The prepared highly active TiB X The α-TiO2 nanocomposite precursor reacts with silicon carbide in the liquid phase to form two types of reinforcing phases: first, micron-sized titanium carbide rod-shaped crystals or whiskers are formed through an anisotropic growth process of "dissolution-precipitation" under the catalysis of the liquid phase; second, nanoscale ultrahard boron carbide particles are formed. Simultaneously, the α-silicon nitride in the prepared graphene quantum dot@silicon nitride composite powder also undergoes a phase transition in the liquid environment and grows in situ needle / rod-shaped β-silicon nitride whiskers with large aspect ratios through a dissolution-re-precipitation process. Ultimately, these in-situ formed titanium carbide and β-silicon nitride whiskers interweave within the silicon carbide matrix, contributing to the construction of a three-dimensional micron-scale reinforcing framework.

[0050] Precise control of the interfacial phase is one of the key factors in achieving efficient toughening. Graphene quantum dot@silicon nitride composite powder can play a dual role in this process. On the one hand, the graphene quantum dots on its surface transform into nano-carbon layers at high temperatures. Some of these carbon layers preferentially deposit at the interface between the growing titanium carbide whiskers and the silicon carbide matrix, forming a relatively weakly bonded interfacial layer. This facilitates the reinforcement's participation in energy dissipation through pull-out mechanisms during subsequent crack propagation. On the other hand, these active carbon layers act as templates and promoting factors, interacting with the TiB-derived silicon nitride matrix... X The boron in the -C nanocomposite precursor and the nitrogen generated from the decomposition of silicon nitride react to form two-dimensional layered boron nitride nanosheets. These nanosheets are dispersed at the grain boundaries, providing more deflection paths for crack propagation.

[0051] Finally, the high toughness of the material is related to the synergistic effect of multiple toughening processes. When the material is subjected to external force and microcracks are generated and propagated, their energy can be dissipated through the following processes: 1) When the crack tip encounters the diffusely distributed hard boron carbide nanoparticles, it is pinned, increasing the propagation resistance; 2) When the crack propagates along the grain boundary, it is forced to deflect and twist when it encounters two-dimensional boron nitride nanosheets, thus prolonging the propagation path; 3) When the crack crosses the matrix, it encounters the titanium carbide and β-silicon nitride whisker framework, resulting in crack bridging and inhibiting crack opening; 4) As the crack further propagates, thanks to the presence of relatively weak bonding interfaces, these whiskers are gradually pulled out of the matrix, and this process consumes a lot of fracture energy through frictional work; 5) A small amount of Y-La-Si-OB amorphous glass phase formed after sintering and cooling exists at the grain boundary, which plays a role in passivation and slow release of crack tip energy.

[0052] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0053] In the early stages of sintering, the self-made yttrium-lanthanum dual rare earth boride additive reacts with the silica on the surface of silicon carbide to form a low-melting-point Y-La-Si-OB liquid phase. This liquid phase encapsulates the particles and promotes mass transfer, which not only helps the material to densify at relatively low temperatures, but also creates the necessary conditions for the in-situ generation of various reinforcing phases.

[0054] In a liquid phase environment, TiB X -C nanocomposite precursors react with graphene quantum dots@silicon nitride composite powder to form a multi-dimensional, multi-scale reinforcing structure: TiB X -C precursors can generate micron-sized titanium carbide whiskers and nano-sized boron carbide particles; simultaneously, α-silicon nitride in graphene quantum dot@silicon nitride composite powder can grow micron-sized needle-like β-silicon nitride whiskers through phase transformation. The interlacing of these two types of whiskers helps to form a three-dimensional reinforcing framework inside the material;

[0055] The regulation of the interfacial phase by graphene quantum dot@silicon nitride composite powder can be used as an important way to toughen the material: the converted carbon nanolayers form a relatively weak bonding interface around the titanium carbide whiskers, which is conducive to the whisker pull-out effect during the toughening process; on the other hand, these carbon layers also promote the reaction of boron and nitrogen to form two-dimensional boron nitride nanosheets, which helps to introduce crack deflection effect.

[0056] The high toughness of the silicon carbide ceramic composite material of this application stems from the synergistic effect of multiple toughening processes within it: when cracks propagate, they are first affected by boron carbide particle pinning and amorphous phase passivation at grain boundaries, and then deflected by two-dimensional boron nitride nanosheets; finally, the titanium carbide and silicon nitride whisker framework further absorbs fracture energy through crack bridging and the key whisker pull-out effect, thereby helping to suppress brittle fracture of the material. Detailed Implementation

[0057] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The embodiments described herein are specific implementations of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limiting the implementation of the present invention or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application. These technical solutions include technical solutions that employ any obvious substitutions and modifications made to the embodiments described herein.

[0058] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing.

[0059] Example 1

[0060] This embodiment provides a high-toughness silicon carbide ceramic composite material and its preparation method. The preparation method of the high-toughness silicon carbide ceramic composite material specifically includes the following steps:

[0061] S1: Titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder were ball-milled with anhydrous ethanol at high energy to obtain a precursor mixture slurry; wherein the molar ratio of titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder was 1:2.3:5.2, the ball milling speed was 380 rpm, and the ball milling time was 26 h; the precursor mixture slurry was vacuum dried at 85 °C to obtain a pre-prepared precursor, which was then heat-treated at 980 °C for 2.2 h at a rate of 5.5 °C / min under an inert atmosphere, and after natural cooling, it was ground and sieved to obtain TiB. X -C nanocomposite precursor;

[0062] S2: Citric acid and urea were dispersed in deionized water at a mass ratio of 1:2.1 to obtain reaction solution A. The reaction solution was hydrothermally reacted at 185℃ for 9 hours. After centrifugation and purification, a graphene quantum dot dispersion was obtained. α-Silicon nitride was added to deionized water to prepare an α-silicon nitride suspension. The graphene quantum dot dispersion was then added dropwise to the α-silicon nitride suspension to obtain reaction solution B. The amount of citric acid added was 12% of the mass of α-silicon nitride. After adjusting the pH value to 4.8, the mixture was magnetically stirred for 4.5 hours and then vacuum dried at 88℃ to obtain graphene quantum dot@silicon nitride composite powder.

[0063] S3: Yttrium nitrate, lanthanum nitrate, boric acid, and citric acid were dispersed in deionized water to obtain a sol; wherein the molar ratio of yttrium nitrate to lanthanum nitrate was 1.05:1, the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to boric acid was 1:6.1, and the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to citric acid was 1:1.55; the sol was heated in a water bath at 82℃ and the pH was adjusted to 7.8 with 8wt.% ammonia to obtain a gel; after drying the gel, it was pre-carbonized at 620℃ for 2.3h at a rate of 3.5℃ / min under nitrogen protection to obtain a crude product, and then the temperature was further increased to 1480℃ at a rate of 5.2℃ / min and held for 3.2h. After cooling, it was purified to obtain yttrium-lanthanum double rare earth boride solid solution nanoparticles;

[0064] S4: Silicon carbide, TiB X A composite slurry was prepared by wet mixing of γ-C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol using anhydrous ethanol as the medium; among which, silicon carbide and TiB... X The mass ratio of -C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol was 87:5:3:2.0:1.0. Wet mixing was performed at 320 rpm for 13 hours. The composite slurry was vacuum dried at 86℃ and sieved to obtain composite granulated powder. The composite granulated powder was loaded into a graphite mold and placed in a spark plasma sintering furnace, where a vacuum of 5 × 10⁻⁶ was applied. -2 Pa; The temperature was increased to the sintering temperature of 1850℃ at a rate of 110℃ / min and held for 9min, while a uniaxial pressure of 55MPa was applied during the heating process; the high-toughness silicon carbide ceramic composite material was obtained by furnace cooling under the pressure.

[0065] Example 2

[0066] This embodiment provides a high-toughness silicon carbide ceramic composite material and its preparation method. The preparation method of the high-toughness silicon carbide ceramic composite material specifically includes the following steps:

[0067] S1: Titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder were ball-milled with anhydrous ethanol at high energy to obtain a precursor mixture slurry; wherein the molar ratio of titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder was 1:2.1:4.5, the ball milling speed was 300 rpm, and the ball milling time was 20 h; the precursor mixture slurry was vacuum dried at 70 °C to obtain a pre-prepared precursor, which was then heat-treated at 900 °C for 1.5 h at a rate of 4 °C / min under an inert atmosphere, and after natural cooling, it was ground and sieved to obtain TiB. X -C nanocomposite precursor;

[0068] S2: Citric acid and urea were dispersed in deionized water at a mass ratio of 1:1.8 to obtain reaction solution A. The reaction solution was hydrothermally reacted at 170℃ for 6 hours. After centrifugation and purification, a graphene quantum dot dispersion was obtained. α-Silicon nitride was added to deionized water to prepare an α-silicon nitride suspension. The graphene quantum dot dispersion was then added dropwise to the α-silicon nitride suspension to obtain reaction solution B. The amount of citric acid added was 5% of the mass of α-silicon nitride. After adjusting the pH value to 4, the mixture was magnetically stirred for 3 hours and then vacuum dried at 70℃ to obtain graphene quantum dot@silicon nitride composite powder.

[0069] S3: Yttrium nitrate, lanthanum nitrate, boric acid, and citric acid were dispersed in deionized water to obtain a sol; wherein the molar ratio of yttrium nitrate to lanthanum nitrate was 0.9:1, the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to boric acid was 1:5.8, and the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to citric acid was 1:1.4; the sol was heated in a 75°C water bath and the pH was adjusted to 7 with 12wt.% ammonia water to obtain a gel; after drying the gel, it was pre-carbonized at 550°C for 1.5h at a rate of 2°C / min under nitrogen protection to obtain a crude product, and then the temperature was further increased to 1400°C at a rate of 4°C / min and held for 2.5h. After cooling, it was purified to obtain yttrium-lanthanum double rare earth boride solid solution nanoparticles;

[0070] S4: Silicon carbide, TiB X A composite slurry was prepared by wet mixing of γ-C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol using anhydrous ethanol as the medium; among which, silicon carbide and TiB... X The mass ratio of -C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol was 90:6:4:2.5:1.2. Wet mixing was performed at 250 rpm for 10 hours. The composite slurry was vacuum dried at 70°C and sieved to obtain composite granulated powder. The composite granulated powder was loaded into a graphite mold and placed in a spark plasma sintering furnace, where a vacuum of 1×10⁻⁶ was applied. -1 Pa; The temperature was increased to the sintering temperature of 1750℃ at a rate of 80℃ / min and held for 6min, while a uniaxial pressure of 40MPa was applied during the heating process; the high-toughness silicon carbide ceramic composite material was obtained by furnace cooling under the pressure.

[0071] Example 3

[0072] This embodiment provides a high-toughness silicon carbide ceramic composite material and its preparation method. The preparation method of the high-toughness silicon carbide ceramic composite material specifically includes the following steps:

[0073] S1: Titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder were ball-milled with anhydrous ethanol at high energy to obtain a precursor mixture slurry; wherein the molar ratio of titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder was 1:2.4:4.8, the ball milling speed was 320 rpm, and the ball milling time was 22 h; the precursor mixture slurry was vacuum dried at 75 °C to obtain a pre-prepared precursor, which was then heat-treated at 920 °C for 1.8 h at a rate of 4.5 °C / min under an inert atmosphere, and after natural cooling, it was ground and sieved to obtain TiB. X -C nanocomposite precursor;

[0074] S2: Citric acid and urea were dispersed in deionized water at a mass ratio of 1:1.9 to obtain reaction solution A. The reaction solution was hydrothermally reacted at 175℃ for 7 hours. After centrifugation and purification, a graphene quantum dot dispersion was obtained. α-Silicon nitride was added to deionized water to prepare an α-silicon nitride suspension. The graphene quantum dot dispersion was then added dropwise to the α-silicon nitride suspension to obtain reaction solution B. The amount of citric acid added was 8% of the mass of α-silicon nitride. After adjusting the pH value to 4.2, the mixture was magnetically stirred for 3.5 hours and then vacuum dried at 78℃ to obtain graphene quantum dot@silicon nitride composite powder.

[0075] S3: Yttrium nitrate, lanthanum nitrate, boric acid, and citric acid were dispersed in deionized water to obtain a sol; wherein the molar ratio of yttrium nitrate to lanthanum nitrate was 0.95:1, the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to boric acid was 1:5.9, and the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to citric acid was 1:1.45; the sol was heated in a water bath at 78℃ and the pH was adjusted to 7.2 with 15wt.% ammonia to obtain a gel; after drying the gel, it was pre-carbonized at 580℃ for 1.7h at a rate of 2.5℃ / min under nitrogen protection to obtain a crude product, and then the temperature was further increased to 1420℃ at a rate of 4.8℃ / min and held for 2.8h. After cooling, it was purified to obtain yttrium-lanthanum double rare earth boride solid solution nanoparticles;

[0076] S4: Silicon carbide, TiB X A composite slurry was prepared by wet mixing of γ-C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol using anhydrous ethanol as the medium; among which, silicon carbide and TiB... X The mass ratio of -C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol was 85:4:2:1.5:0.8. Wet mixing was performed at 280 rpm for 11 hours. The composite slurry was vacuum dried at 76℃ and sieved to obtain composite granulated powder. The composite granulated powder was loaded into a graphite mold and placed in a spark plasma sintering furnace, where a vacuum of 8 × 10⁻⁸ ppm was applied. -3Pa; The temperature was increased to the sintering temperature of 1780℃ at a rate of 90℃ / min and held for 7min, while a uniaxial pressure of 45MPa was applied during the heating process; the high-toughness silicon carbide ceramic composite material was obtained by furnace cooling under the pressure.

[0077] Example 4

[0078] This embodiment provides a high-toughness silicon carbide ceramic composite material and its preparation method. The preparation method of the high-toughness silicon carbide ceramic composite material specifically includes the following steps:

[0079] S1: Titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder were ball-milled with anhydrous ethanol at high energy to obtain a precursor mixture slurry; wherein the molar ratio of titanium dioxide nanoparticles, amorphous boron powder, and carbon black powder was 1:2.2:5.5, the ball milling speed was 400 rpm, and the ball milling time was 28 h; the precursor mixture slurry was vacuum dried at 90 °C to obtain a pre-prepared precursor, which was then heat-treated at 1000 °C for 2.5 h at a rate of 6 °C / min under an inert atmosphere, and after natural cooling, it was ground and sieved to obtain TiB. X -C nanocomposite precursor;

[0080] S2: Citric acid and urea were dispersed in deionized water at a mass ratio of 1:2.2 to obtain reaction solution A. The reaction solution was hydrothermally reacted at 190℃ for 10 hours. After centrifugation and purification, a graphene quantum dot dispersion was obtained. α-Silicon nitride was added to deionized water to prepare an α-silicon nitride suspension. The graphene quantum dot dispersion was then added dropwise to the α-silicon nitride suspension to obtain reaction solution B. The amount of citric acid added was 15% of the mass of α-silicon nitride. After adjusting the pH value to 5, the mixture was magnetically stirred for 5 hours and then vacuum dried at 90℃ to obtain graphene quantum dot@silicon nitride composite powder.

[0081] S3: Yttrium nitrate, lanthanum nitrate, boric acid, and citric acid were dispersed in deionized water to obtain a sol; wherein the molar ratio of yttrium nitrate to lanthanum nitrate was 1.1:1, the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to boric acid was 1:6.2, and the molar ratio of the total molar amount of yttrium nitrate and lanthanum nitrate to citric acid was 1:1.6; the sol was heated in an 85°C water bath and the pH was adjusted to 8 with 5wt.% ammonia water to obtain a gel; after drying the gel, it was pre-carbonized at 650°C for 2.5 h at a rate of 4°C / min under nitrogen protection to obtain a crude product, and then heated to 1500°C at a rate of 6°C / min and held for 3.5 h. After cooling, it was purified to obtain yttrium-lanthanum double rare earth boride solid solution nanoparticles;

[0082] S4: Silicon carbide, TiB XA composite slurry was prepared by wet mixing of γ-C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol using anhydrous ethanol as the medium; among which, silicon carbide and TiB... X The mass ratio of -C nanocomposite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles, and polyvinyl alcohol was 88:5.5:3.5:2.2:1.1. Wet mixing was performed at 350 rpm for 14 hours. The composite slurry was vacuum dried at 90℃ and sieved to obtain composite granulated powder. The composite granulated powder was loaded into a graphite mold and placed in a spark plasma sintering furnace, where a vacuum of 1×10⁻⁶ was applied. -3 Pa; The temperature was increased to the sintering temperature of 1900℃ at a rate of 120℃ / min and held for 10min, while a uniaxial pressure of 60MPa was applied during the heating process; the high-toughness silicon carbide ceramic composite material was obtained by furnace cooling under the pressure.

[0083] Comparative Example 1

[0084] This comparative example provides a high-toughness silicon carbide ceramic composite material, which differs from Example 1 in that titanium carbide powder and boron carbide powder are used to replace TiB in equal amounts. X -C nanocomposite precursor, other operating steps and process parameters are exactly the same as in Example 1.

[0085] Comparative Example 2

[0086] This comparative example provides a high-toughness silicon carbide ceramic composite material. The difference between this example and Example 1 is that no graphene quantum dot@silicon nitride composite powder is added. All other operating steps and process parameters are exactly the same as in Example 1.

[0087] Comparative Example 3

[0088] This comparative example provides a high-toughness silicon carbide ceramic composite material. The difference from Example 1 is that silicon nitride nanopowder is used instead of graphene quantum dot@silicon nitride composite powder. Other operating steps and process parameters are exactly the same as in Example 1.

[0089] Comparative Example 4

[0090] This comparative example provides a high-toughness silicon carbide ceramic composite material. The difference from Example 1 is that the alumina-yttrium oxide mixed powder is used instead of the yttrium-lanthanum double rare earth boride solid solution nanoparticles, wherein the mass ratio of alumina to yttrium oxide is 2:3. Other operating steps and process parameters are exactly the same as in Example 1.

[0091] The performance of the high-toughness silicon carbide ceramic composite materials of Examples 1-4 and Comparative Examples 1-4 was tested, and the specific process is as follows:

[0092] The hardness of the sample was tested according to GB / T16534-2009;

[0093] The fracture toughness of the test samples was determined according to GB / T23806-2009;

[0094] The flexural strength of the test sample was determined according to GB / T6569-2006.

[0095] The test results are shown in Table 1.

[0096] Table 1. Performance test results of high-toughness silicon carbide ceramic composite materials prepared in Examples 1-4 and Comparative Examples 1-4

[0097] Hardness (GPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Flexural strength (MPa) Example 1 28.8 4.5 520 Example 2 28.5 4.6 510 Example 3 28.4 4.4 505 Example 4 28.3 4.3 520 Comparative Example 1 24.5 2.2 250 Comparative Example 2 29.2 3.0 310 Comparative Example 3 29.0 3.6 390 Comparative Example 4 25.5 2.8 260

[0098] From the test results of Example 1 and Comparative Example 1 in Table 1, it can be seen that replacing TiB with equal amounts of titanium carbide powder and boron carbide powder... X -C nanocomposite precursors exhibit reduced hardness, fracture toughness, and flexural strength. This is because physically blended hard particles readily form macroscopic agglomerates, which become primary defects within the material after sintering. Cracks propagate rapidly along these defects, leading to decreased fracture toughness and deteriorating flexural strength. The decrease in hardness is directly related to the low density of the agglomerated regions.

[0099] As shown in Table 1, the test results of Example 1 and Comparative Example 2 reveal that without the addition of graphene quantum dots@silicon nitride composite powder, the hardness slightly increases, while the fracture toughness and flexural strength decrease. The increase in hardness is due to the increased relative content of the high-hardness phase in the system. The deterioration in fracture toughness is due to the simultaneous absence of the toughening effects of silicon nitride phase transformation, whisker pull-out induced by weak interface modulation, and crack deflection caused by boron nitride nanosheets. The decrease in flexural strength is due to the weakened resistance of the material to defect propagation.

[0100] As shown in Table 1, the test results of Example 1 and Comparative Example 3 indicate that replacing the graphene quantum dot@silicon nitride composite powder with silicon nitride nanopowder slightly increases the hardness, but decreases both fracture toughness and flexural strength. The increase in hardness is related to the low formation amount of relatively soft phases such as the graphene-converted carbon layer and boron nitride in the system. Although the phase transformation toughening effect of silicon nitride still exists, the lack of graphene quantum dots makes it difficult or insufficient to form the nano-carbon layer used for interface control and the boron nitride nanosheets used for crack deflection. This weakens the toughening effect: due to the insufficient weak interface layer, the titanium carbide whiskers are more strongly bonded to the matrix, making them more prone to brittle fracture rather than pull-out during crack propagation, thus hindering the whisker pull-out effect; simultaneously, the insufficient formation of two-dimensional boron nitride also weakens the crack deflection effect. Therefore, its flexural strength is also weakened due to the reduced toughness, making it difficult to effectively suppress the propagation of internal microcracks.

[0101] As shown in Table 1, the test results of Example 1 and Comparative Example 4 reveal that replacing the yttrium-lanthanum double rare earth boride solid solution nanoparticles with alumina-yttrium oxide mixed powder (where the mass ratio of alumina to yttrium oxide is 2:3) resulted in a decrease in performance. This is because traditional oxide additives primarily provide a liquid-phase sintering environment to promote densification, and are less likely to participate in in-situ reactions and form a corresponding chemical environment as effectively as boride additives. Due to differences in the liquid-phase chemical environment (insufficient active boron source), TiB... X The in-situ reaction of the -C precursor and the formation of subsequent reinforcing phases are suppressed. Therefore, although the material can be densified, it is difficult to fully construct an effective multi-scale reinforcing structure inside, resulting in a relative reduction in its mechanical properties.

[0102] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a high-toughness silicon carbide ceramic composite material, characterized in that, The preparation method includes: S1: Titanium dioxide nanopowder, amorphous boron powder and carbon black powder are ball-milled and heat-treated in a molar ratio of 1:(2.1-2.4):(4.5-5.5) to obtain a titanium boron carbon composite precursor; S2: Graphene quantum dots were prepared by reacting citric acid and urea; graphene quantum dots were then reacted with α-silicon nitride suspension to obtain graphene quantum dot@silicon nitride composite powder. S3: Yttrium nitrate, lanthanum nitrate, boric acid and citric acid were gelled, dried, heat-treated and purified to obtain yttrium-lanthanum double rare earth boride solid solution nanopowder; S4: Silicon carbide, titanium boron carbon composite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles and polyvinyl alcohol are wet-mixed to obtain a composite slurry; dried and sieved to obtain composite granulated powder; and then plasma sintered to obtain a high-toughness silicon carbide ceramic composite material.

2. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S1: The ball milling process involves mixing titanium dioxide nanopowder, amorphous boron powder, carbon black powder, and anhydrous ethanol, and then high-energy ball milling them in a ball mill to obtain a precursor mixture slurry. The heat treatment involves vacuum drying the precursor mixture slurry to obtain a pre-prepared precursor, followed by heat treatment at an inert atmosphere.

3. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S2: The mass ratio of citric acid to urea is 1:(1.8-2.2).

4. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S2: The amount of citric acid added is 5-15% of the mass of α-silicon nitride; The graphene quantum dots were prepared by hydrothermal reaction of citric acid and urea dispersed in deionized water. The graphene quantum dot@silicon nitride composite powder is prepared by adding graphene quantum dots to an α-silicon nitride suspension, adjusting the pH, and then stirring the mixture to react.

5. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S3: The gelation process involves dispersing yttrium nitrate, lanthanum nitrate, boric acid, and citric acid in deionized water to obtain a sol, which is then heated and the pH adjusted with ammonia to obtain a gel. The heat treatment is a process in which the gel is dried and then heated under nitrogen protection. The molar ratio of yttrium nitrate to lanthanum nitrate is (0.9-1.1):

1.

6. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S3: The total molar amount of yttrium nitrate and lanthanum nitrate is in a molar ratio of 1:(5.8-6.2) to boric acid.

7. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S3: The total molar amount of yttrium nitrate and lanthanum nitrate is in the molar ratio of citric acid to 1:(1.4-1.6).

8. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S4: The plasma sintering is the sintering of the composite granulated powder under vacuum with uniaxial pressure applied during the heating process; The mass ratio of silicon carbide, titanium boron carbon composite precursor, graphene quantum dot@silicon nitride composite powder, yttrium-lanthanum double rare earth boride solid solution nanoparticles and polyvinyl alcohol is (85-90):(4-6):(2-4):(1.5-2.5):(0.8-1.2).

9. The method for preparing a high-toughness silicon carbide ceramic composite material according to claim 1, characterized in that, In S4: The vacuum degree during the sintering of the composite granulated powder is 10. -1 -10 -3 Pa; The sintering temperature of the composite granulated powder is 1750-1900℃.

10. A high-toughness silicon carbide ceramic composite material prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of graphene quantum dot-nanoparticle-epoxy resin composite material

    CN111073221A

  • Ultrahigh-temperature ceramic with long-time ablation resistance and toughness and preparation method thereof

    CN118388255A